PENGARUH EMPLOYEE ENGAGEMENT DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. TUNAS DWIPA MATRA MANADO - sambuaga, imanuelah kartika; pio , Riane Johnly; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS, 2026)
The decline in productivity and low employee loyalty at PT. Tunas Dwipa Matra indicate problems in human resource management. This study aims to analyze the effect of employee engagement and organizational commitment on employee performance. A quantitative approach was used, involving 52 employees as the research sample. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares with SmartPLS 3.0. The results show that all constructs meet validity and reliability requirements. Furthermore, employee engagement and organizational commitment have a positive and significant effect on employee performance, both partially and simultaneously. These findings emphasize that enhancing employee engagement and organizational commitment is a key factor in improving sustainable employee performance.